Effect of Organizational Culture and Managerial Competence on Performance of Lecturerin Obstetrics Study Program at Private University of North Sumatera - Aktar, Salim (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to determine the effect of: (1) organizational culture on performance of lecturer, and (2) managerial competence of lecturer on performance of lecturer. Subjects were lecturers at study program of obstetrics of Private University in North Sumatera, with a total sample of 172 respondents. Tool measuring instruments used in data retrieval organizational culture, managerial competence by using a Likert scale questionnaire. For performance data used direct observation to lecturers of obestetrics program at Private University in North Sumatera. Before the research instrument used in this study, it tested first, followed by validity and reliability testing. To test the validity questionnaire used calculation formula product moment, and to test the reliability of the questionnaire used alpha formula. Coefficientreliability of Organizational culture questionnaire is 0.921 and coefficientreliability of managerial competence is 0.904. Thus the instruments are the very high category questionnaire. To test the hypothesis proposed in this study used the techniques of correlation and path coefficient. Based on hypothesis tested,it can be concluded that there is a direct and significant effect: (1) organizational culture on performance of lecturer with path coefficient = 0.222, (2) managerial competence of lecturer on performance of lecturer with path coefficient of 0,156.